RANCANGAN INSTALASI PENGOLAHAN AIR LIMBAH INDUSTRI TEPUNG AREN DI KABUPATEN KLATEN PROVINSI JAWA TENGAH SEBAGAI ALTERNATIF PENGELOLAAN LINGKUNGAN - , Donan Wijaya, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the characteristics of liquid waste of palm flour industry, to know the distribution of industrial liquid waste, to calculate the amount of liquid waste discharge, and to plan the system of wastewater treatment plant (WWTP).